Pelatihan Implementasi Pembelajaran Mendalam (Deep Learning) dalam Pengajaran Bahasa Inggris di MGMP Madrasah Aliyah DIY: Indonesia - Rahayu, Puji; Murtafi'ah, Banatul; Prasetya, Willy; Widyastuti, Nur (UII, 2026)
This community service program aims to address the pedagogical barriers faced by Madrasah Aliyah (MA) English teachers in DIY when implementing Deep Learning. The primary issue was the teachers' conceptual confusion and lack of operational guidance in designing meaningful learning experiences. The implementation method spanned ten weeks through collaboration with the DIY MA English Teacher Forum (MGMP), involving needs analysis, practical module development based on Tomlinson’s principles, and a series of workshops on classroom management, material development, assessment, and artificial intelligence (AI) integration. Results demonstrated a significant transformation in teacher capacity, shifting from rote-based instruction to more contextual and student-centered instructional designs. Program evaluation through post-tests and reflective discussions confirmed that participants successfully internalized the Deep Learning principles, i.e., mindful, meaningful, and joyful within their teaching instruments. The program's implication is significant, providing practical modules (print and digital) and a digital repository of teaching kits as sustainable community assets. In conclusion, this MGMP-based community empowerment effectively altered teachers' mindsets and professional practices. This model holds strategic implications for replication in other subjects within the madrasah environment, creating a systemic impact on improving education quality towards a more humanistic and profound approach.